Peningkatkan Aktivitas Siswa Pada Penerapan Model Discovery Learning Materi Pemanfaatan Perangkat Lunak Presentasi - Siswanto, Agus (FKIP Unirow Tuban, 2022)
This research was conducted in class XII AKL SMK Negeri 2 Tuban. This research was conducted from October to November 2019 in the odd semester of the 2019/2020 school year. The subjects of this study amounted to 36 students. The object of this research is the active learning of class XII AKL students, in ICT learning activities. This research uses Classroom Action Research. In this study, an observation instrument was used to measure the level of active learning of class XII AKL students. After being applied to cycles I and II, the results showed that in cycle I, the criteria for action research had not yet been achieved. While in the second cycle, the improvement of class XII AKL students has reached the minimum criteria for research success that have been determined. In the Very High category of learning activity, there are 4 students. In the high category of learning activity, there are 27 students. Enough category, there are 3 students. However, there are still 2 students with low learning activity levels. The results in the second cycle is a very rapid increase, the article, in the pre-cycle and first cycle, there is not a single student with a very high level of learning activity. On the other hand, at the pre-cycle stage, there were as many as 80.6% of students who got the Low category of learning activity in learning activities.